Numerical and experimental analysis of a novel heat pump driven sorption storage heater - Aydin, Devrim; Casey, Sean P.; Chen, Xiangjie; Riffat, Saffa (Elsevier, 2018)
This study investigates a hybrid “solid sorption heat storage/air sourced heat pump” system for energy efficient heating of buildings. The proposed system could convert excess energy generated using photovoltaic panels/off-peak electricity to heat and charge the sorption material to store that heat for later use. The novel heat recovery process employed in the system enables high heat storage efficiency through condensation of desorbed moisture in a heat storage charging cycle.